Covariation in Couples’ Nightly Sleep and Gender Differences - Lee, Soomi (Sleep Health, 2017)
OBJECTIVES: For most partnered adults, sleep is not an individual-level behavior―it is a shared health behavior with a partner. This study examined whether perceived nightly sleep duration and sleep quality covaried within couples and whether the unique influence of partner sleep on individual sleep differed by gender. DESIGN: Eight consecutive days of diary data. PARTICIPANTS: U.S. hotel employees and their spouses/partners (N=76 from 38 couples, 600 daily observations) MEASUREMENTS: Each day, couples separately reported their previous night’s sleep duration (in hours) and sleep quality (1=very unsatisfactory to 5=very satisfactory). Analyses adjusted for sociodemographic, family, work, and day-level characteristics. RESULTS: Dyadic multilevel modeling revealed positive covariation in nightly sleep duration within couples. After controlling for the effects of contextual covariates, partner influence on individual sleep duration was more apparent in men’s sleep. When a female’s sleep duration was longer or shorter than usual, their male partner’s sleep duration was also longer or shorter than usual, respectively. However, a female’s sleep was not significantly predicted by her male partner’s sleep duration, after taking into account the effects of her sleep on the male partner’s sleep and contextual covariates. Sleep quality covaried on average across days between partners, and this association did not differ by gender. CONCLUSIONS: Our results demonstrate positive covariation in sleep duration and sleep quality within couples. Couples’ sleep duration covaried night-to-night and their sleep quality covaried on average across days. A male’s sleep duration is predicted by the female partner’s sleep duration, but not vice versa. Future research should examine health consequences of couple sleep covariation.